PENGEMASAN PRODUK WISATA OLEH POKDARWIS SEBAGAI SALAH SATU MODEL PARIWISATA ALTERNATIF - Andiani, Nyoman Dini; Widiastini, Ni Made Ary (Jurnal Kewirausahaan dan Bisnis, 2017)
A Conscious Tourism Group in Indonesia called Kelompok Sadar Wisata (Pokdarwis) is one of the groups in society that has an important role and contribution in tourism development in a region. The existence of Pokdarwis in the tourist destination should get support and guidance either by the community itself, government, academy and investors. This is so that Pokdarwis can play a more effective role in helping to mobilize the community in realizing the environment and atmosphere that is conducive to the growth and development of tourism activities in tourist destinations. Buleleng District there are 12 Pokdarwis which in practice still needs to get attention from various parties. On this occasion, the Ipteks for Society (IbM) program, which is an annual program implemented by a university, can be a means of providing services to the community regarding issues that arise in the group. Through this IbM program, two Pokdarwis, such as Pokdarwis Tunjung Mekar and Pokdarwis Bhuana Shanti, have just developed physical potential, requiring assistance and training to maximize the potential of their village. In this case the two groups are not well understood for the package tour, so based on the condition, IbMs programme is a means to arrange the community to create package including marketing strategies. Understood the disadvantages of guiding guides that guide travelers who ask them to use a foreign language, then the IbM program is created guidebook in two languages and Indonesian. Through participatory approaches various forms of training and guidance on how to package tourism, holiday techniques and marketing strategies can be done well.